The Effect of Electricity Supply Interruptions on Small Business Productivity in West Sumatra - Hamid, Muhammad Imran; Sulfandri; Afifah (Jurusan Teknik Elektro Universitas Andalas, 2023)
This research examines the impact of interruptions in electricity supply on the production of small and medium enterprises in West Sumatra from 2014 to 2021. The data used in the research was obtained from the Ministry of Trade and Industry of West Sumatra, including the production variables, employment, investment, and other variables that influence the production activities. A regression equation connecting production factors and production levels is formulated. Furthermore, another regression equation is also formulated by considering the electricity interruption factor, namely the SAIDI index on production levels. The effect of electrical power interruptions is then evaluated by comparing the two equations. The research results show that the most significant production loss occurred in 2019, 16.07 hours/year, while the most negligible loss occurred in 2015, 6.53 hours/year. Trend data collected during the research period regarding loss conditions and interruption parameters shows that electricity disturbances do not have a linear impact on production losses. The research also shows that electric power does not significantly impact the production activities of small and medium enterprises in West Sumatra.